Jawabanmu

2014-08-23T22:54:28+07:00
  \left[\begin{array}{ccc}2a.2b&-2ab&\\2ab&2a-2b&\end{array}\right] =  \left[\begin{array}{ccc}-1&0&\\0&-1&\end{array}\right] -   \left[\begin{array}{ccc}a&-b&\\b&a&\end{array}\right]  \\  \\  \left[\begin{array}{ccc}2a.2b&-2ab&\\2ab&2a-2b&\end{array}\right]=\left[\begin{array}{ccc}-1-a&b&\\-b&-1-a&\end{array}\right] \\  jadi : \\ 2ab=-b \\ 2a= \frac{-b}{b}  \\ 2a=-1 \\ a= \frac{1}{2}  \\  \\ 2a-2b=-1-a \\ 2 \frac{1}{2}  -2b=-1- \frac{1}{2}  \\ -2b=-1- \frac{1}{2} -1 \\ -2b=- \frac{1}{2} \ b=-\frac{1}{4}
soalnya nggak salah kah??? punya saya a^2.b^2 sama , a^2-b^2